An Analysis of Factors Related to Receipt of Accommodations and Services by Postsecondary Students With Disabilities. (July 2015) - Newman, Lynn A.; Madaus, Joseph W.
A secondary analysis of the National Longitudinal Transition Study–2 examined the relationship between demographic, disability-related, secondary school preparation, and transition planning variables and receipt of accommodations and other disability-specific services at the postsecondary level for 2, 470 postsecondary students with disabilities. The results indicated that secondary students who received transition planning education were more likely to receive accommodations and other disability-specific services in 2-year colleges and that those who had a transition plan that specified postsecondary accommodations and supports as a needed post–high school service were more likely to receive those types of services in 2-year colleges and in career and technical education schools. These findings suggest that secondary schools can influence the likelihood that students will seek out and receive postsecondary accommodations and other disability-specific services.